Calculus for business, economics, and the social and life sciences - Hoffmann, Laurence D. (McGraw-Hill, 2007)
Calculus for Business, Economics, and the Social and Life Sciences" introduces calculus in real-world contexts and provides a sound, intuitive understanding of the basic concepts students need as they pursue careers in business, the life sciences, and the social sciences.